A Literary Review of Amavata - Rana, Reetika; Kumar, Parveen; Sharma, Chander Shekhar; Kumari, Smita (International Research Journal of Ayurveda & Yoga, 2022)
Ayurveda is an ancient system of medicine that deals with the prevention as well as treatment of the diseases through natural ways. This science is well known for its role in mentioning the techniques for better lifestyle viz. seasonal regimen, daily regimen and Achar Rasayana etc without causing any side effect. The word Amavata is made up of two words Ama and Vata. Ama means toxins that are formed as an end product of poor digestion which then circulates in the body and gets accumulated in Shleshamsthana i.e., Sandhi Sthana where it shows it’s effects like stiffness, pain and many more. The term ‘Vata’ in the disease Amavata indicates aggravated Vata Dosha in the body. Just like air takes clouds from one place to another place, similarly Vata dosha take rest of the Dosha i.e. Pitta and Kapha from one place to another. Although there is no direct description about the diseases Amavata given in the Brihattrayi but the term ‘Amavata’ is given in the indications of some formulations. Acharya Yogratnakara and Acharaya Chakrapani described the treatment of Amavata in which they mentioned the use of Langhana Karma, Swedana Karma, Tikta, Katu and Deepan drugs, Virechana drugs and Basti Karma.All the above-mentioned treatments have the properties to cure aggravated Vata dosha and Ama in the body. The present paper throws a light on the various aspects of Amavata explained in the ancient Ayurveda texts. Nidana, Samprapti, Lakshna and all the treatment options mentioned in the Ayurveda Samhitas are highlighted here